Estado del Arte de la Gestión administrativa: Avances y Retos para las Empresas Colombianas del Sector de la Construcción (2015)
This document makes a very brief approach to practices, models, methodologies and developed bodies of knowledge in Administration, related to the Management and Organizational Development, to determine which of these, have been implemented or received by the Management of construction companies. After such review, it was identified that methodologies such as the business model, the lean Startup, customer development, experience design, and others have not been applied, according to the literature, such practices Management of Construction Companies . With these results, it became an expert consultation to determine the potential use of these methodologies in the construction sector, obtaining encouraging results for the tested methodologies.